2016
DOI: 10.1589/jpts.28.1472
|View full text |Cite
|
Sign up to set email alerts
|

Early reduction in toe flexor strength is associated with physical activity in elderly men

Abstract: [Purpose] To compare the toe flexor, hand grip and knee extensor strengths of young and elderly men, and to examine the association between toe flexor strength and physical activity or inactivity levels. [Subjects and Methods] Young (n=155, 18–23 years) and elderly (n=60, 65–88 years) men participated in this study. Toe flexor, hand grip, and knee extensor strength were measured. Physical activity (time spent standing/walking per day) and inactivity (time spent sitting per day) were assessed using a self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Another possibility is that such associations are linked to the physical activity level and/or gait speed. Toe flexor strength reflects the level of physical activity [9, 12] and gait speed [5]. Physical activity intervention reduces the risk of type 2 diabetes and hypertension [44].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another possibility is that such associations are linked to the physical activity level and/or gait speed. Toe flexor strength reflects the level of physical activity [9, 12] and gait speed [5]. Physical activity intervention reduces the risk of type 2 diabetes and hypertension [44].…”
Section: Discussionmentioning
confidence: 99%
“…Toe flexor strength is associated with the amount of low-to-moderate intensity physical activity [9, 12]. A previous study showed that toe flexor strength/BM in a higher daily step counts group (≥8000) was greater than that in a lower daily step counts group, however, such a difference in knee extensor strength/BM was not observed in women aged 52–78 years [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations